Land and spirituality in rabbinic literature (Leiden ; Boston)
xvi, 321 sayfa
Keywords: “This volume is devoted to the texts, traditions, and practices of the Land of Israel from the end of the Second Temple period through late antiquity. Based upon a conference organized by the Yeshiva University Center for Israel Studies, this collection uses a range of critical methodologies and sources, including the Palestinian and Babylonian Talmudim, archaeology, and Samaritan and Jewish liturgical poetry. It presents a vibrant, complex, and multi-layered series of snapshots of rabbinic culture, written by leading contemporary scholars.“ --